2018
DOI: 10.1002/jts.22328
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Outcome and Residual Symptoms Following Trauma‐Focused Psychotherapy in Police Officers With Posttraumatic Stress Disorder

Abstract: Police officers exposed to potentially traumatic events (PTE) are at a heightened risk of developing posttraumatic stress disorder (PTSD). Little is known about trauma‐focused psychotherapy outcomes in the police. In this naturalistic study, we evaluated whether PTE exposure and baseline clinical characteristics predicted PTSD symptom reduction during treatment and residual PTSD symptoms posttreatment. In consecutive referrals to a specialized mental health service for police officers (N = 665), PTSD was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 48 publications
2
31
0
Order By: Relevance
“…Although three studies did not show significant treatment effects (47)(48)(49), 19 studies revealed significant treatment effects on symptom reduction. It is important to note that, with the exception of Smid et al (50), the reported effects concerned the entire treatment and not only the ritual element(s). This means that the studies reported here measured effects in terms of reductions in grief or other symptoms after completion of the full treatment, not only the ritual element.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although three studies did not show significant treatment effects (47)(48)(49), 19 studies revealed significant treatment effects on symptom reduction. It is important to note that, with the exception of Smid et al (50), the reported effects concerned the entire treatment and not only the ritual element(s). This means that the studies reported here measured effects in terms of reductions in grief or other symptoms after completion of the full treatment, not only the ritual element.…”
Section: Discussionmentioning
confidence: 90%
“…As can be seen in Appendix 1, 8 studies were categorized level 2 of evidence (RCT with significant symptom reduction), 11 studies were categorized as level 3 evidence (non-randomized controlled cohort/follow-up study) and three studies were categorized as level 4 due to no significant result of the treatment [one RCT with no significant effect; (47), two pre/post-tests with no significant result due to small sample; (48,49)]. All measured effects were reported for the entire treatment, with the exception of one observational study that measured a significant separate effect on the ritual element (farewell ritual) (50).…”
Section: Evidence Levels For Grief Therapies With Ritual Elementsmentioning
confidence: 99%
“…Hence, no model fit indices for the model are given. This model fits prior research using a comparable sample and design (46). For the calculation of Cohen's d (47), we used the mean and standard deviation of the change in symptoms during treatment and the correlation between pre-and posttreatment symptoms for all measures (48).…”
Section: Data Analysesmentioning
confidence: 99%
“…Of all mental health conditions experienced by police officers, PTSD has received the most clinical and research attention (Gersons et al, 2000;Difede et al, 2007). In addition, PTSD and prolonged grief are often comorbid as shown by a growing body of research (e.g., Wenzel, 2002;Gibson, 2008;Nakajima et al, 2012); however, it appears that PTSD symptom reduction may be more challenging in the treatment context when such comorbidity exists (Smid et al, 2018). Despite the treatment challenge when PTSD and prolonged grief are comorbid, PTSD evidence-based treatment (e.g., Cognitive-Behavioral Therapy, Exposure Therapy) has been shown to be significantly efficacious in PTSD symptom improvement among first responders who suffer from PTSD (Gersons et al, 2000;Difede et al, 2007).…”
Section: Prolonged Grief Vs Post-traumatic Stress Disordermentioning
confidence: 99%
“…Most police officers may not ultimately be diagnosed with PTSD, however, most officers experience loss at some point during their law enforcement careers. Nevertheless, especially in the context of specialized police mental health services with a focus on PTSD, specific attention should be emphasized to the mental health effects of losses of loved ones on police officers' mental health and well-being (Smid et al, 2018).…”
Section: Prolonged Grief Vs Post-traumatic Stress Disordermentioning
confidence: 99%